Biochemical and pharmacological similarities between the venoms of newborn Crotalus durissus durissus and adult Crotalus durissus terrificus rattlesnakes - Gutiérrez, José María (1991)
A comparative study was performed with the venoms of newborn Crotalus durissus durissus, adult Crotalus durissus terrificus and adult Crotalus durissus durissus snakes. Venom of newborn specimens of C.d. durissus is very similar to that of adult specimens of C.d. terrificus, since they have strong lethal and myotoxic activities, and weak proteolytic, hemorrhagic and edema-forming effects, in contrast to venom of adult specimens of C.d. durissus. In addition, the two former venoms have high amounts of the neurotoxic complex crotoxin, whereas venom from adult C.d. durissus has a low concentration of crotoxin. Electrophoretic analysis corroborates the strong similarities between the former two venoms. It is concluded that venom of newborn C.d. durissus contains high concentrations of crotoxin and low amounts of hemorrhagic and proteolytic components, and that a drastic ontogenetic change takes place in the venom composition of this subspecies.